Teaching diversity in citizenship education: Context-related teacher understandings and practices. (February 2019) - Sincer, Işıl; Severiens, Sabine; Volman, Monique
Abstract: Many secondary schools address diversity as an aspect of citizenship education. This paper examines how secondary teachers' understandings and practices concerning teaching about diversity are related to school contextual factors, such as student composition and educational track. Semi-structured interviews with 17 teachers at three schools revealed that teachers' understandings and practices regarding diversity are related to their perceptions of the needs and capabilities of their student population. However, teachers rarely addressed diversity in terms of deep-rooted issues, such as inequality and power relations. The paper concludes with implications for teachers and schools and provides suggestions for future research. Highlights: Teachers' diversity-related practices are largely influenced by the school context. Teachers' diversity-related understandings are less strongly dependent on the school context. Teachers' understandings and practices are related to their perceptions of the students. Teachers rarely addressed deep-rooted issues such as inequality and power relations. Implications for teachers and schools are discussed.